2005
DOI: 10.1111/j.1600-6143.2005.00972.x
|View full text |Cite
|
Sign up to set email alerts
|

Human CD4+CD25+ Regulatory T Cells Suppress Anti‐Porcine Xenogeneic Responses

Abstract: Due to the shortage of human organs, xenotransplantation is being explored as an alternative to allotransplantation, but immune rejection remains a major hurdle to its implementation. We tested the ability of human CD4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(36 citation statements)
references
References 21 publications
(30 reference statements)
2
34
0
Order By: Relevance
“…In alloimmune responses, these FoxP3 þ Tregs have been shown to suppress CD4 þ and CD8 þ T cells as well as many other cell types including antigen-presenting cells, dendritic cells, B cells and macrophages [44][45][46]. In-vitro studies of the human T-cell responses to porcine cells have shown that CD4 þ CD25 þ Tregs were able to suppress the CD4 þ CD25 À T-cell proliferative response as well as inhibit their secretion of IFN-g, TNF-a, IL-2, IL-10 and IL-6 [47]. Wu et al [48 ] extended these findings by showing that expanded human CD4 þ CD25 þ Tregs maintained their regulatory capacity and expressed high levels of FoxP3.…”
Section: The Role Of Regulatory T Cells In Xenotransplantationmentioning
confidence: 99%
“…In alloimmune responses, these FoxP3 þ Tregs have been shown to suppress CD4 þ and CD8 þ T cells as well as many other cell types including antigen-presenting cells, dendritic cells, B cells and macrophages [44][45][46]. In-vitro studies of the human T-cell responses to porcine cells have shown that CD4 þ CD25 þ Tregs were able to suppress the CD4 þ CD25 À T-cell proliferative response as well as inhibit their secretion of IFN-g, TNF-a, IL-2, IL-10 and IL-6 [47]. Wu et al [48 ] extended these findings by showing that expanded human CD4 þ CD25 þ Tregs maintained their regulatory capacity and expressed high levels of FoxP3.…”
Section: The Role Of Regulatory T Cells In Xenotransplantationmentioning
confidence: 99%
“…Recent studies have shown that human Treg are capable of suppressing CD4 ? CD25 -effector T cell-mediated anti-pig cellular response in vitro (Porter and Bloom 2005;Sun et al 2010a, b;Wu et al 2008) and that adoptive transfer with in vitro polyclonally expanded human Treg prevents islet xenograft rejection by suppressing effector T cell responses (Yi et al 2012). This raises the possibility that Treg may be used therapeutically at the time of xenotransplantation to reduce the requirement of systemic immunosuppression (Muller et al 2012;O'Connell et al 2010;Muller et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Clinical Cancer Research, the same research team used this model to examine the capacity of human Treg to control x-GVHD in vivo (1). Previous experiments had shown the capacity of human Treg to suppress proliferation of autologous CD4 + CD25 À T cells in response to porcine xenogeneic stimulation (29). No model had yet tested the function of these cells in vivo, however.…”
mentioning
confidence: 97%